Regulatory Reform in Mexico's Natural Gas Industry : Liberalization in the Context of a Dominant Upstream Incumbent - Halpern, Jonathan (The World Bank, 1999)
January 2001 - Liberalization of the natural gas industry is complex because the sector combines activities with natural monopoly characteristics with activities that are potentially competitive. The challenges are compounded when the State opts to retain vertically integrated monopolies in otherwise contestable segments of the industry. Regulatory issues associated with partial liberalization of natural gas markets are analyzed through a case study of Mexico. The natural gas industry combines activities with natural monopoly characteristics with those that are potentially competitive. Pipeline transport and distribution, which have natural monopoly characteristics, require regulation of price and nonprice behavior. Production is a contestable activity, but in a few countries (including Mexico) it remains a state monopoly. Gas marketing is also contestable, but the presence of a dominant, upstream, vertically integrated incumbent may pose significant barriers to entry. Market architecture decisions—such as horizontal structure, regional development, and the degree of vertical integration—are also crucial. Rosellón and Halpern report that Mexico has undertaken structural reform in the energy sector more slowly than many other countries, but it has introduced changes to attract private investment in natural gas transport and distribution. These changes were a response to the rapid growth in demand for natural gas (about 10 percent a year) in Mexico, which was in turn a response to economic development and the enforcement of environmental regulations. The new regulatory framework provides incentives for firms to invest and operate efficiently and to bear much of the risk associated with new projects. It also protects captive consumers and improves general economic welfare.